Preclinical Models of Cancer Therapy–Associated Cardiovascular Toxicity: A Scientific Statement From the American Heart Association. Issue 1 (25th June 2021) - Asnani, Aarti; Moslehi, Javid J.; Adhikari, Bishow B.; Baik, Alan H.; Beyer, Andreas M.; de Boer, Rudolf A.; Ghigo, Alessandra; Grumbach, Isabella M.; Jain, Salvia; Zhu, Han
Abstract : Although cardiovascular toxicity from traditional chemotherapies has been well recognized for decades, the recent explosion of effective novel targeted cancer therapies with cardiovascular sequelae has driven the emergence of cardio-oncology as a new clinical and research field. Cardiovascular toxicity associated with cancer therapy can manifest as a broad range of potentially life-threatening complications, including heart failure, arrhythmia, myocarditis, and vascular events. Beyond toxicology, the intersection of cancer and heart disease has blossomed to include discovery of genetic and environmental risk factors that predispose to both. There is a pressing need to understand the underlying molecular mechanisms of cardiovascular toxicity to improve outcomes in patients with cancer. Preclinical cardiovascular models, ranging from cellular assays to large animals, serve as the foundation for mechanistic studies, with the ultimate goal of identifying biologically sound biomarkers and cardioprotective therapies that allow the optimal use of cancer treatments while minimizing toxicities. Given that novel cancer therapies target specific pathways integral to normal cardiovascular homeostasis, a better mechanistic understanding of toxicity may provide insights into fundamental pathways that lead to cardiovascular disease when dysregulated. The goal of this scientific statement is to summarize the strengths and weaknesses of preclinical models of cancer therapy–associated cardiovascular toxicity, to highlight overlapping mechanisms driving cancer and cardiovascular disease, and to discuss opportunities to leverage cardio-oncology models to address important mechanistic questions relevant to all patients with cardiovascular disease, including those with and without cancer.